دور العلاقات العامة في تحقيق اهداف البعثات الدبلوماسية بالسودان : دراسة تطبيقية لمجموعة من السفارات العربية والأجنبية بالخرطوم - آدم، فاطمة آدم أبكر (2016)
This study under the title, "The Role of Public relationship on the diplomatic sector: Applied study on the number of both Arabic and foreign Embassy in Khartoum. During the period 2014-2016." This study aims at knowing the role of public relationship in the Diplomatic sector and to know the relationship that link the public relationship organ with diplomacy and the international communication process and the international administration techniques of the public relations, where as modern diplomacy is know by being the art of administration of communication and relations between states and that modern diplomacy stands of mass media and public relations. The study is done in Khartoum which is the capital city including all embassies. (22) Arabic and foreign embassies, (2) consulates and (6) corporations relate to diplomatic field in Sudan were chosen. the researcher used the analytic, surgical method and the comparative method. the questionnaire is used for data collection and interviews with responsible and some interested in the information and diplomatic domain . The study had come out to a number of results, mainly: the reviews responses showed a concern from Arabic and foreign embassies for having a post of public relation is an issue of diplomatic job,, Where as the percentage of on need is very little that due to vagueness for the actual post of public relation employee in embassy- a section or a big administration including ( public relation manager, protocols and procedures- occasions- marketing and seruices). The results showed that public relation personal use the internet and the modern mass-media so often. The study about whether the employee should be qualified for the post of public relation or not, some interferes claiming that anyone who smartness and ability to precede comfily the post. After the theoretical and empirical study, the researcher come out with some re commendations: Efficiency of the public relation post to be including, coordination evaluation – follow-up- observation- not only offering seruices. Three should be coordination between the embassy media and the diplomatic department and the corporations of the hosting country.